'There is no progression in prevention' – The experiences of mental health nurses working with repeated self-harm. - Doyle, Louise; Keogh, Brian; Murphy, Caroline (My University, 2019)
Caring for people who self‐harm is an everyday experience for mental health nurses and an important part of their role. How mental health nurses respond to and support those who self‐harm can have a significant impact on the outcomes for service users and their intentions to seek help in the future. Repeated self‐harm can be a particularly challenging phenomenon as it is often misunderstood and can have a negative impact on the therapeutic relationship. This qualitative descriptive study aims to explore how mental health nurses understand and work with repeated self‐harm. Nine nurses working in a range of mental health settings within one service participated in semi‐structured interviews which were analysed thematically. Findings are presented in two themes exploring participants’ perceptions and understanding of repeated self‐harm, and the process of learning to work with repeated self‐harm, and are reported in accordance with the consolidated criteria for reporting qualitative research guidelines (COREQ). Participants reported that nursing practice relating to repeated self‐harm remains largely focused on maintenance of safety and prevention of self‐harm despite the identification that this often does not work. It was accepted that there is sometimes a lack of understanding about the function of self‐harm; however, participants reported understanding increased following specific education about self‐harm. Participants also identified the potential for more empowering and recovery‐orientated responses, including the utilization of harm reduction approaches, to the care of those who repeatedly self‐harm.
PUBLISHED
Keywords: Harm reduction; Mental health nurses; Repeated self-harm; Self-harm; Self-harm